Ulization of Coconut coir and Guava Leaves For The Natural Preservation of Palm Sugar - Risaluna Arianda Br.Purba; M. Idris (Jurnal Biologi Tropis, 2023)
The Coconut coir contains active compounds that can inhibit bacterial activity, namely tannins. Guava leaves can inhibit microbial growth because they contain flavonoids, triterpenoids, saponins, tannins, and eugenol. The purpose of this study was to find out the use of coconut coir for the natural preservation of palm sap, to find out the use of guava leaves, and to find out the combination of using coconut coir and guava leaves for the natural preservation of palm sap. This research was carried out in June-July 2022 in Prestasi District, Langkat Regency, North Sumatra Province. This study used a randomized block design (RBD) method, with two factors, namely the addition of coconut fiber (K) and guava leaves (J), each consisting of 3 treatments, namely: K0 = 0gr; K1 = 80gr; K2 = 120gr; J0 = 0gr; J1 = 5gr; J2 = 10gr with 3 repetitions. The results showed that the use of 5 grams of coconut coir in preserving palm sap was beneficial in maintaining a pH value above 6 and lower sugar content of 13.6 °Brix. The use of guava leaves of as much as 120 grams is useful in reducing the water content in palm sap up to 84.00%. The use of a combination of coconut coir and guava leaves is beneficial in reducing the water content in palm sap, which is 82.00%.